The Effectiveness of Lore Traditional Games Towards The Ability to Recognize The Concept of Numbers on Early Childhood - Jhoni Warmansyah; Zulhendri Zulhendri; Amalina Amalina (Ta'dib, 2021)
This study aims at finding out the effectiveness of traditional Lore games on the ability to recognize the concept of numbers in kindergarten. This research used a quantitative approach implemented in the form of the quasi-experimental method with a pretest-posttest design. The population of this study is all early childhood students of group B in South Pariaman District, Pariaman City. Sample withdrawal technique using simple random sampling. Data collection techniques use a test of the ability to recognize the concept of numbers that self-designed, refer to aspects and indicators.  Hypothetical testing using data analysis techniques is a paired t-test by looking at each difference from the average score comparison. The result shows that traditional Lore games are effective in developing the ability to recognize the concept of numbers in early childhood. Therefore, the use of traditional games can be a strategy for teachers to teach math, particularly about the concept of numbers.